Olanzapine Induced Hair Loss: A Case Report - Kuloglu, Murat; Korkmaz, Sevda; Kilic, Nilufer; Saglam, Sema; Gurok, M. Gurkan; Atmaca, Murad (Kure Iletisim Grubu A S, 2012)
Olanzapine induced hair loss: a case report Drug-induced alopecia is a side effect characterized by generalized hair loss. It is reversible when the drug is discontinued. Among psychotropic agents, this side-effect is most often reported with the use of valproic acid and lithium. There are limited reports on atypical antipsychotic-induced hair loss. Here, we report a case of hair loss after olanzapine use which resolved after the discontinuation of olanzapine.
olanzapin kullanımına ba?lı saç dökülmesi: Bir olgu sunumu
Keywords: Olanzapine; alopecia; side effects